Cell-free expression, purification, and membrane reconstitution for NMR studies of the nonstructural protein 4B from hepatitis C virus - Fogeron, Marie-Laure; Jirasko, Vlastimil; Penzel, Susanne; Paul, David; Montserret, Roland; Danis, Clément; Lacabanne, Denis; Badillo, Aurélie; Gouttenoire, Jérôme; Moradpour, Darius; Bartenschlager, Ralf; Penin, François; et al. (Journal of biomolecular NMR, 2016)
We describe the expression of the hepatitis C virus nonstructural protein 4B (NS4B), which is an integral membrane protein, in a wheat germ cell-free system, the subsequent purification and characterization of NS4B and its insertion into proteoliposomes in amounts sufficient for multidimensional solid-state NMR spectroscopy. First spectra of the isotopically [2H,13C,15N]-labeled protein are shown to yield narrow 13C resonance lines and a proper, predominantly α-helical fold. Clean residue-selective leucine, isoleucine and threonine-labeling is demonstrated. These results evidence the suitability of the wheat germ-produced integral membrane protein NS4B for solid-state NMR. Still, the proton linewidth under fast magic angle spinning is broader than expected for a perfect sample and possible causes are discussed.
Gesehen am 20.05.2020